Studi Karakteristik Mekanik Komposit Kayu Randu Bermatrik Asam Sitrat - Much Suranto; Darupratomo Darupratomo; Ratnanik Ratnanik (Pusat riset dan Inovasi Nasional, 2026)
This paper was made to explain the results of research on how to obtain the most appropriate citric acid adhesive composition in the manufacture of randu wood fiber composites in order to obtain a strong and suitable composite material. The research was carried out by experimental methods in the laboratory through a series of mechanical tests, namely the bending strength test and the screw grip strength test. The sample specimen is 5 cm × 20 cm × 1 cm for flexural strength testing and 5 cm × 10 cm × 1 cm for screw grip strength test. Composite specimens were made with variations in the composition of citric acid adhesives of 2.5%, 5%, 7.5%, 10%, 12.5%, 15%, 17.5%, and 20% by weight of randu wood. The results showed that the composite of randu wood particles with a citric acid matrix had optimal strength at a certain ratio, which was 7.5%. At the same ratio, the test results of the screw grip strength test also provide the highest value. These findings confirm that the exact composition of the adhesive has a significant impact on the final performance of the resulting composite.